2011
DOI: 10.4315/0362-028x.jfp-11-032
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Quality of Water Immersion-Chilled and Air-Chilled Broilers

Abstract: Carcass chilling during broiler processing is a critical step in preventing growth of pathogenic and spoilage bacteria. The objective of this study was to compare the microbiological quality of air- and water-chilled broiler carcasses processed at the same commercial facility. For each of four replications, 15 broilers were collected from the same commercial processing line after evisceration, after spraying with cetylpyridinium chloride (a cationic disinfectant), and after air chilling or water immersion chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 41 publications
2
16
0
Order By: Relevance
“…Chilling is a step for inhibiting pathogens during broiler processing (Sánchez and others ; Zhang and others ). Eviscerated carcasses are normally chilled by a water immersion or air chilling system.…”
Section: Resultsmentioning
confidence: 99%
“…Chilling is a step for inhibiting pathogens during broiler processing (Sánchez and others ; Zhang and others ). Eviscerated carcasses are normally chilled by a water immersion or air chilling system.…”
Section: Resultsmentioning
confidence: 99%
“…Poultry meats will be contaminated with bacteria through attachment of feces during the processing course, and the contaminated meats will release these bacteria into the environment, and non-contaminated meats will thereby be contaminated [19, 25]. Once bacteria attached to the meats, it was difficult to kill the bacteria on meats [14, 30]. It is desirable to kill bacteria immediately before attachment to the other meats.…”
Section: Discussionmentioning
confidence: 99%
“…Tsai et al [27] and Northcutt et al [22] reported that chiller tanks at the processing plants contained around 0.35 or 0.16% suspended solids, respectively. Although chicken is chemically sanitized during processing and subsequently cleaned before packaging, some microorganisms cannot be removed completely, especially bacteria strongly attached to chicken skin [5, 14, 23, 30]. This is because these microorganisms, including Salmonella and Campylobacter, are able to become entrapped in deep skin layers, crevices, or feather follicles, thus becoming protected from chemical agents [5, 15, 29].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…can occur at various stages of poultry processing such as scalding, defeathering, evisceration, and chilling (Lillard, 1989;Hafez et al, 1997;Ono and Yamamoto, 1999;Buhr et al, 2005;McKee, 2012). Although chicken is chemically sanitized during processing and subsequently cleaned before packaging, some microorganisms cannot be removed completely, especially for bacteria strongly attached to chicken skin (Ko et al, 2005;Zhang et al, 2011). This is because these microorganisms including Salmonella and Campylobacter are able to become entrapped in deep skin layers, crevices, or feather follicles, thus becoming protected from chemical agents (Krysinski et al, 1992;Mosteller and Bishop, 1993;Yang et al, 2001;Chantarapanont et al, 2004).…”
Section: Introductionmentioning
confidence: 98%